TiO2 derived by titanate route from electrospun nanostructures for high-performance dye-sensitized solar cells - Nair, A. Sreekumaran (2013)
We report the use of highly porous, dense, and anisotropic TiO2 derived from electrospun TiO2–SiO2 nanostructures through titanate route in dye-sensitized solar cells. The titanate-derived TiO2 of high surface areas exhibited superior photovoltaic parameters (efficiency > 7%) in comparison to the respective electrospun TiO2 nanomaterials and commercially available P-25.